On asymmetric information and tax morale in developing countries - Ahmed Salim Nuhu; John M. Musah (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2018)
Our paper investigates the implications of asymmetric non-tax revenue information for tax morale using micro data from thirty-six African countries. We utilize a model in which agents form their perceptions about the sufficiency of government non-tax revenue for development financing under asymmetric information conditions. We then construct a composite index of information access that generates predictions about these perceptions and tax morale at the household level. Two important predictions emerge: (i) in the presence of asymmetric information, households overestimate the ability of non-tax revenues alone to finance development, which (ii) has significant negative effects on household-level tax morale. Our findings - which are robust across specifications and controls of cross-country fixed differences in tax morale - provide evidence that improvement in government information supply regarding the use of non-tax revenues, beyond annual budget readings and households tax obligations, could significantly enhance tax morale and compliance.
Keywords: H26; H31; P35; 330; Tax morale; mediation analysis; asymmetric information; principal component analysis